2009
DOI: 10.1093/pch/14.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing fetal alcohol spectrum disorder: History, challenges and future directions

Abstract: Fetal alcohol spectrum disorder (FASD) is one of the most common preventable causes of developmental disability, and is currently one of the most pressing public health concerns in Canada. FASD refers to the range of physical, mental, behavioural and learning disabilities that an individual may acquire as a result of maternal alcohol consumption. In the present paper, the history of the diagnostic approach to alcohol-related disorders over the past 35 years is reviewed. Research supporting the importance of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 63 publications
1
51
0
1
Order By: Relevance
“…The majority of retrospective studies incorporated no information about the dosage, timing or duration of exposure, only a known history of maternal alcohol consumption reported by mothers or caregivers [138]. Another parameter not available in a number of studies is socioeconomic status (SES) which is known related to alcohol consumption patterns [139].…”
Section: Insights From Radiological Studies Of Humans With Fasdmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of retrospective studies incorporated no information about the dosage, timing or duration of exposure, only a known history of maternal alcohol consumption reported by mothers or caregivers [138]. Another parameter not available in a number of studies is socioeconomic status (SES) which is known related to alcohol consumption patterns [139].…”
Section: Insights From Radiological Studies Of Humans With Fasdmentioning
confidence: 99%
“…Studies in humans with FASD, even when obtained prospectively, cannot incorporate precise information about drinking quantities; moreover, virtually all drinking women drink repeatedly during pregnancy rather than at only a single time-point [138]. Animal models, on the other hand, have allowed specific investigations of the effects of PAE with respect to the quantity (from mild to heavy drinking), timing and duration of ethanol exposure during development, and demonstrated that the CNS exhibits varied vulnerability to ethanol insult across gestation [145].…”
Section: Accepted Manuscript 25 3 Radiological Studiementioning
confidence: 99%
“…fetal alcohol spectrum disorder; prenatal alcohol exposure; methyl metabolism; developmental programming; hypothalamo-pituitary axis; glucocorticoid receptor; serotonin transporter FETAL ALCOHOL SPECTRUM DISORDER (FASD) is a serious public health issue that is estimated to affect 9.1 individuals in every 1,000 live births in the United States (6). FASD is a nondiagnostic term describing the broad range of deficits in neurobehavioral and cognitive function found in children exposed to alcohol in utero.…”
mentioning
confidence: 99%
“…The diagnosis of the effects of alcohol intake during pregnancy at birth or during child development is still a challenge (1,2) . The events described by Jones and Smith in the early 1970s (3) included changes in pre-and/or post-natal development such as facial dysmorphia (undefined philtrum, palpebral fissures, thin upper lip, flattened face) and dysfunction of the central nervous system (CNS) (intellectual disabilities and/or attention deficit).…”
Section: Introductionmentioning
confidence: 99%